Turnover Intentions? Symptoms on Job Satisfaction and Job Insecurity in The Face of a Pandemic - Saputra, Arief Dwi; Rahmatia, Alfina; Surwanti, Arni (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2021)
Turnover intention is the permanent resignation of employees voluntarily (voluntary) or not (involuntary) from an organization. In fact, human resources are an investment for the organization. This study will attempt to review the symptoms that occur during a pandemic through a review of Turnover Intentions obtained by job satisfaction and job imperfections. This study aims to see the effect of job satisfaction and job insecurity on turnover intentions in the case study of the Presidium business unit. The object of this research is the Marketing Executive with a saturated sample technique method and a questionnaire to 158 respondents. Data were analyzed using the SPSS 22 application, traffic conclusions with multiple data analysis techniques. The results of this study can ignore that the variables of job satisfaction and job insecurity have a positive influence on turnover intention. This explains that Turnover Intentions are a symptom that occurs during a pandemic. The implications for the findings of the review results can be used as insights for organizations in facing a pandemic period and can become a future research agenda for a more comprehensive organizational review.